2018
DOI: 10.3846/bjrbe.2018.384
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Vehicle Multi-Body Dynamic Simulations to Estimate Skidding Distance

Abstract: Abstract. The skid mark is valuable for accident reconstruction as it provides information about the braking behaviour drivers and the speed of heavy vehicles. However, despite its importance, there is currently no mathematical model available to estimate skidding distance (SD) as a function of vehicle characteristics and road conditions. This paper attempts to develop a non-linear regression model that is capable of reliably predicting the skidding distance of heavy vehicles under various road conditions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…From the research method of braking performance, Zamzamzadeh et al [27] estimated the vehicle's slip distance by performing a multi-body dynamics simulation on the vehicle. Suh et al [28] showed a braking performance simulation on a semi-trailer tractor.…”
Section: Introductionmentioning
confidence: 99%
“…From the research method of braking performance, Zamzamzadeh et al [27] estimated the vehicle's slip distance by performing a multi-body dynamics simulation on the vehicle. Suh et al [28] showed a braking performance simulation on a semi-trailer tractor.…”
Section: Introductionmentioning
confidence: 99%